Antecedent Factors That Increase Customer Loyalty (Case Study of Mie Gacoan Restaurant) - Noviany, Fanny; Muhmin, Andi Hidayat; Sofyan, Joel Faruk (Journal of Current Research In Multidisciplinary, 2024)
In Indonesia, spicy food is a rapidly growing business. Mie Gacoan is one of the restaurants that serves spicy noodle dishes. Customer loyalty in the food business sector is influenced by several factors, including product quality, service quality, brand image, promotion, price fairness, and customer satisfaction. This study aims to test the influence of product quality, service quality, brand image, promotion, and price fairness on customer satisfaction and customer loyalty at the Mie Gacoan restaurant. The analysis method used is PLS-SEM. The population of this study was consumers who had purchased Mie Gacoan products. Respondents were determined using the purposive sampling method, with a total of 168 respondents. The results of this study indicate that product quality, service quality, promotion, and price fairness have a positive effect on customer satisfaction and customer loyalty. The subsequent results show that brand image does not influence customer satisfaction, and promotion does not influence customer loyalty. The limitations of this study include its focus on only a few aspects affecting customer satisfaction and loyalty. Additionally, respondents are not evenly distributed across age ranges and are limited to the Jabodetabek area. Therefore, it is suggested that further research can expand aspects that can affect customer satisfaction and customer loyalty, such as trust, store atmosphere, and physical environment quality. Further research can also expand the research area, and a larger number of respondents is needed.